Proinflammatory and cytotoxic response to nanoparticles in precision-cut lung slices - Hirn, Stephanie; Haberl, Nadine; Loza, Kateryna; Epple, Matthias; Kreyling, Wolfgang G.; Rothen-Rutishauser, Barbara; Rehberg, Markus; Krombach, Fritz (Beilstein Journal of Nanotechnology, 2014)
Precision-cut lung slices (PCLS) are an established ex vivo alternative to in vivo experiments in pharmacotoxicology. The aim of this study was to evaluate the potential of PCLS as a tool in nanotoxicology studies. Silver (Ag-NPs) and zinc oxide (ZnO-NPs) nanoparticles as well as quartz particles were used because these materials have been previously shown in several in vitro and in vivo studies to induce a dose-dependent cytotoxic and inflammatory response. PCLS were exposed to three concentrations of 70 nm monodisperse polyvinylpyrrolidone (PVP)-coated Ag-NPs under submerged culture conditions in vitro. ZnO-NPs (NM110) served as ‘soluble’ and quartz particles (Min-U-Sil) as ‘non-soluble’ control particles. After 4 and 24 h, the cell viability and the release of proinflammatory cytokines was measured. In addition, multiphoton microscopy was employed to assess the localization of Ag-NPs in PCLS after 24 h of incubation. Exposure of PCLS to ZnO-NPs for 4 and 24 h resulted in a strong decrease in cell viability, while quartz particles had no cytotoxic effect. Moreover, only a slight cytotoxic response was detected by LDH release after incubation of PCLS with 20 or 30 µg/mL of Ag-NPs. Interestingly, none of the particles tested induced a proinflammatory response in PCLS. Finally, multiphoton microscopy revealed that the Ag-NP were predominantly localized at the cut surface and only to a much lower extent in the deeper layers of the PCLS. In summary, only ‘soluble’ ZnO-NPs elicited a strong cytotoxic response. Therefore, we suggest that the cytotoxic response in PCLS was caused by released Zn2+ ions rather than by the ZnO-NPs themselves. Moreover, Ag-NPs were predominantly localized at the cut surface of PCLS but not in deeper regions, indicating that the majority of the particles did not have the chance to interact with all cells present in the tissue slice. In conclusion, our findings suggest that PCLS may have some limitations when used for nanotoxicology studies. To strengthen this conclusion, however, other NP types and concentrations need to be tested in further studies.
Keywords: cytokines; cytotoxicity; ex vivo; lung slices; nanoparticles